2004
DOI: 10.1023/b:jarg.0000031246.76666.f6
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Semen Characteristics on the Success of Intrauterine Insemination

Abstract: Purpose : To evaluate the influence of sperm characteristics on the outcome of infertility treatment using intrauterine insemination (IUI). Methods : Retrospective study of 431 infertility couples who underwent 1007 IUI treatment cycles from June 1999 to October 2002. Sperm parameters before and after preparation for IUI were evaluated and correlated with pregnancy outcome. Results : Clinical pregnancy occurred in 12% of cycles and 28% of patients. Initial sperm motility and processed forward progression were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
37
0
6

Year Published

2006
2006
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 15 publications
5
37
0
6
Order By: Relevance
“…Intrauterine insemination is widely used for treating infertility in couples because it is a simple, inexpensive, and acceptable assisted reproductive technique (1). There are variety of indications for IUI such as poor male factor, cervical hostility, and unexplained infertility.…”
mentioning
confidence: 99%
“…Intrauterine insemination is widely used for treating infertility in couples because it is a simple, inexpensive, and acceptable assisted reproductive technique (1). There are variety of indications for IUI such as poor male factor, cervical hostility, and unexplained infertility.…”
mentioning
confidence: 99%
“…We found out that morphology itself could predict 68.4% of pregnant cases, +4 volatile sperm rate 69.6% and +3 volatile sperm rate 33.0%. Aligned with our study, Zhao et al [17] also reported in their study that sperm motility in the initial sperm sample was an independent factor that could affect pregnancy with IUI. They emphasized the importance of the existence of +3 and +4 motile sperm in the washed semen for the success of IUI.…”
Section: Discussionsupporting
confidence: 89%
“…In fertility studies, the 1 to 5 ͑slowest-to-fastest͒ speed of progression ͑SOP͒ score is often used to characterize overall motility of a semen sample and to assess sperm quality. 1 This kind of scoring system is subjective and can be replaced by a quantitative measure based on objective computer scoring system.…”
Section: Introductionmentioning
confidence: 99%